The temperature effect on dielectric parameters of bent-core liquid crystal (DHB) - Canli, Nimet Yilmaz; Ocak, Hale; Yildiz, Alptekin; Okutan, Mustafa; Eran, Belkiz Bilgin (ELSEVIER, 2017)
In this study, we have been analyzed in detail the dielectric, ac conductivity properties and phase transition temperatures of the bent-core liquid crystal 3'-{4-[4-(3,7-Dimethyloctyloxy)benzoyloxy]benzoyloxy}-4-{4-[4-[11-(1,1,1,3,5,5,5-heptamethyltrisiloxan-3-yl)undec-1-yloxy]benzoyloxy]benzoyloxy}biphenyl (DHB) exhibiting a dark conglomerate mesophase (DC[*(]) phase) by Impedance Spectroscopy measurements at different temperatures. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bent-core liquid crystal; Impedance Spectroscopy (IS); Dark conglomerate mesophase; CONDUCTIVITY; Chemistry; Physics